Derivational morphology in Tshivenda: an analysis of word-formation processes. - Nengovhela, Matodzi Alpheus (My University, 2005)
Word-building falls into two broad categories, namely, derivation, (the creation of lexical items) and inflection (the creation of grammatical words). This study focuses on derivational morphology in Tshivenda. It reflects an analysis of different word-formation processes such as affixation, compounding, zeroderivation, back formation, clipping, blending, acronym, adoption of brand names as common words, borrowing, anomatopoeia, transposition, and stress-shift. This work shows that Tshivenda derivations enable us to form new words by recycling the pre-existing material (morphemes and words), that is, to add new lexical items to the open word-classes such as nouns and verbs. It will also be evident from this work that it is possible to create new words in Tshivenda by removing or reducing some parts of the words. This work will show how Tshivenda terminology can be updated to cope with the demands of present-day life.
Thesis (M.A. (African Languages)) -- University of Limpopo, 2005
Keywords: Tshivenda language; Grammar, Comparative and general -- Word formation; Tshivenda language -- Dialects -- Morphology